Design Modeling System of Achievement Motivation of Vocational Student Using Radian Basis Function Network Algorithm - Bety Etikasari; Khafidurrohman Agustianto; Trismayanti Dwi Puspitasari; Nanik Anita Mukhlisoh (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2017)
Achievement motivation is one of factor that can influence a person perform to doing their best activities to achieve the goal that has been set. Achievement of learning outcomes that is student ability skills determine from student involvement in the learning process, so the student must be active during their study process. Because of that, by knowing the achievement motivation level is important for the teacher to create the learning environment which suitable to student characteristic so the achievement motivation can be empowered during the learning process. This study, implemented the Radian Basis Function Network (RFBN) to develop the modeling system of student achievement motivation that are high, middle, and low achievement motivation. The study result showed the system accuracy value of 93,09%. Modeling resulted that this student achievement motivation level can be used in education as a reference in determining the learning process for vocational student so that the learning becomes effective and the learning goal can be achieved.